PENGARUH CONTENT MARKETING DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA APLIKASI TIK TOK DI WILAYAH KOTA BIMA - Ismunandar; Sri Ernawati (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Currently, social media is the most popular service among the public. The widespread use of social media has made business people prefer to carry out promotions on online media, especially in providing marketplace services. TikTok Shop is currently in the spotlight because it is part of the services provided by the TikTok application. TikTok launched the TikTok Shop feature on April 17 2021 with the aim of allowing sellers and creators to gain a wide range of potential buyers. This research was conducted in the community in Bima City. Content Marketing and Influencer Marketing as independent variables and Purchase Decisions as the dependent variable. The aim of this research is to find out whether Content Marketing and Influencer Marketing influence purchasing decisions in TikTok application users in the Bima City. The analysis used includes validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient and determination test, t test and f test. The data that has been processed using the SPSS program produces the regression equation Y = 28.278 + 0.299 X1 + 0.197 X2 + 0.05. Based on the t test carried out, it can be seen that Content Marketing and Influencer Marketing simultaneously influence purchasing decisions in TikTok application users in the Bima City.